ASSOCIATION OF AGE, GENDER, STROKE LOCATION, AND SOCIAL SUPPORT WITH DEPRESSION AND COGNITIVE IMPAIRMENT AFTER STROKE - Saeed, Fazal Ur Rahman; Khan, Sikandar Ali; Ayaz, Saeed Bin (Pakistan Armed Forces Medical Journal, 2021)
Objective: To identify depression and cognitive impairment after stroke and analyze association with age, gender, stroke location, and social support. Study Design: A cross-sectional analytical study. Place and Duration of Study: Psychiatry and Rehabilitation Medicine, Combined Military Hospital Gujranwala, from Oct 2015 to Aug 2018. Methodology: Patients (age: 20-80 years) with stroke ≥3 months were included. Those with aphasia, unstable medical history, and coexisting other neurological disorder were excluded. Cognition was assessed by Montreal Cognitive Assessment (MoCA) and post-stroke depression (PSD) was assessed by Beck Depressive Inventory 2nd Edition (BDI-II). Results: Out of 76 patients (meanage: 59 ± 7 years), 53 (69.7%) were male and 23 (30.3%) were females. Fifty-five (72.4%) were of age >55 years and 58 (76.3%) patients had social support. On MoCA evaluation, 41 (53.9%) patients had cognitive impairment. BDI-II assessment showed that 43 (56.6%) individuals had depression. A significantly higher percentage of males, patients without social support, and patients >55 years developed PSD with p<0.05. The cognitive deficit, was statistically significant in the age group of >55 years (p=0.026) and no correlation with gender or presence/absence of social support was observed (p=0.088 and p=0.485 respectively). Similarly, no significant correlation was found between stroke location and development of cognitive deficit or PSD (p=0.361 and p=0.390 respectively). Conclusion: Cognitive impairment and PSD were frequently present after stroke. PSD was more common in males, patients without social support, and patients of older age while cognitive deficit was more common in older age.